Denitrification path and nur in bulkwater phase of municipal sewer networks using natural wastewater. / Salmah Yatim - Yatim, Salmah (2004)
In conventional view, Wastewater Treatment Plants (WWTPs) have been considered as stand-alone units, separate from the sewer system. Treatment, which comprises of physical, chemical and biological processes, is assumed to begin when the wastewater arrives at WWTPs. Recent findings established that wastewater treatment could occur in sewer. Now, sewer accepted to act as a reactor for microbial changes of the wastewater during transport and thereby affects the successive treatment processes or receiving water impacts during combined sewer overflows. It is well known that hydrogen sulfide which is the main source of problems related to odor, human health, toxicity and corrosion of piping and pumping system produced under anaerobic conditions. Anaerobic can be suppressed by adding nitrate to the wastewater to change anaerobic to anoxic condition. The purposes of this study are to verify denitrification pathway in bulkwater phase of sewer networks and to determine nitrate utilization rate (NUR) during anoxic transformations of municipal sewer wastewater. This study is basically of experimental works. The samples for this study are taken from a man-hole near the Civil Engineering Laboratory and wastewater treatment plant located at Jalan Ilmu, UiTM Shah Alam. 2 samples i.e., liquid and gas samples were taken periodically. The liquid samples were analyzed for nitrate (N03) and nitrite (N02), while gas samples were analyzed for nitric oxide (NO) and nitrous oxide (N20). The denitrification pathway of bulkwater phase of municipal sewer networks follows the denitrification pathway of bulkwater proposed by Abdul-Talib et al. (2002). NUR for bulkwater is found to be in the range of 0.396 - 2.123 g N03-N/m3h with the average of 0.829 g N03-N/m3h.